Experimental research on novel RPC-steel composite connections for prefabricated glubam-concrete composite beams. (23rd May 2022) - Shan, B.; Li, T.Y.; Deng, J.Y.; Zou, Y.; Xiao, Y.; Yu, Q.; Zhang, C.Q.
Highlights: Three types of novel connectors, named reactive powder concrete (RPC)-steel composite connectors, were designed and tested for developing fully prefabricated glued laminated bamboo (glubam) and concrete composite (BCC) beams. Experimental results from the push-out tests on the proposed composite connectors with various configurations were presented. This investigation validated that the proposed RPC-steel composite connectors effectively combine the high shear stiffness, high shear capacity and excellent ductility as well as convenient assembly on site. Abstract: This study focused on developing novel connections with high shear stiffness and deformability for fully prefabricated glued laminated bamboo (glubam) and concrete composite (BCC) beams. Three types of reactive powder concrete (RPC)-steel composite connectors were designed and tested in the current investigation. Experimental results from the push-out tests on the proposed composite connectors with various configurations were presented, including the failure modes, shear force-slip responses, shear stiffness, capacity, and ductility. The results indicate that the RPC section can substantially improve the mechanical performance of the composite connectors. Moreover, a type of parametric model was also provided for predicting the shear stiffness and shear capacity of the proposed composite connectors based on the correlation analysis between the configuration parameter and the load bearing efficiency. Compared with the conventional cast-in-situ connectors, the experimental results validated that the easy assembly RPC-steel composite connectors have high shear stiffness and capacity as typical notched type connector as well as the excellent ductility of typical dowel type connector reported in previous studies. Feasibility evaluation revealed that the proposed composite connectors are suitable for a variety of fully prefabricated BCC structures.